Higher Education Distance Learning and e-Learning in Prisons in Portugal - Moreira, J. António (2017)
Higher Education in Europe has undergone massive changes due to technological advancements and adjustments resulting from the Bologna Process, by which learning should be accessible for all regardless of social exclusion reasons, such as imprisonment. The resulting massification of access to Higher Education requires flexible and inclusive training provision focused on the student. These are the primary aims of distance Learning at the open University of Portugal. The aim of this paper is to understand the viewpoints of twenty-six respondents (students, applicants to courses and senior rehabilitation technicians) on the reality of Higher Education in distance Learning and e-Learning in a Portuguese prison. This study occurs in a context of a non-positivist paradigm, placing the emphasis on the perception of individuals through a qualitative methodology. The results obtained from interviews show that the education process has many weaknesses and limitations mostly due to the lack of facilities, educational and technological resources, and support from teachers. The conclusion is that it is essential to provide better conditions for prisoners receiving this type of education, as it can be an opportunity for obtaining professional qualification and for personal development, thus increasing their prospects of success in the future.